EEG as a Predictor of Poorly- Controlled Childhood Epilepsy (Medicine Today, 2020)
Introduction:The aim of the present study was to determine electroencephalographic factors associated with poorly controlled epilepsy.Materials and Methods: This retrospective study was performed from January 2007 to December 2008 at Paediatric Neurology outpatient department in Bangabandhu Sheikh Mujib Medical University, Dhaka, among the children with epilepsy of 7 months to 15 years age who had history of at least 6 months treatment with rational antiepileptic drugs daily with adequate compliance. There were two groups of patients; group 1, consisted of 50 poorly controlled epilepsy patients and group 2, comprised 50 well-controlled epilepsy patients. We retrospectively reviewed EEGs and medical records from these children. Features of initial EEGs findings were compared between the two groups.Results: Significant electroencephalographic predictors of poorly controlled epilepsy were: abnormal initial EEG (p=0.025), EEG background abnormality (p